Expression and regulation of drug transporters in vertebrate neutrophils - Matthew J. Foulkes (Nature Portfolio, 2017)
Abstract There remains a need to identify novel pro-resolution drugs for treatment of inflammatory disease. To date, there are no neutrophil-specific anti-inflammatory treatments in clinical use, perhaps due to our lack of understanding of how drugs access this complex cell type. Here we present the first comprehensive description and expression of both major classes of drug transporters, SLC and ABC, in resting human blood neutrophils. Moreover, we have studied the expression of these carriers in the tractable model system, the zebrafish (Danio rerio), additionally examining the evolutionary relationship between drug transporters in zebrafish and humans. We anticipate that this will be a valuable resource to the field of inflammation biology and will be an important asset in future anti-inflammatory drug design.